Graphite composite polystyrene material and preparation method thereof

By adding a composite graphite composed of graphite of a specific mass ratio, nanosilica and trimethylpropane monoallyl ester to the polystyrene material, the tensile strength of the material is improved, the problem of insufficient tensile strength of the polystyrene material is solved, and its application potential in the automotive interior and aerospace fields is enhanced.

CN119661753AInactive Publication Date: 2025-03-21HEBEI XINTAI NEW MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510187473.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The insufficient tensile strength of polystyrene materials limits its wider application in automotive interiors and aerospace fields.

Method used

By adding composite graphite composed of graphite, nanosilica and trimethylpropane monoallyl ester to the polystyrene material, and limiting its mass ratio to 10:2:0.1~0.3, the tensile strength of the material is improved.

Benefits of technology

The tensile strength of polystyrene materials has been significantly improved, the problem of insufficient tensile strength in the prior art has been solved, and the application potential of the material has been enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and provides a graphite composite polystyrene material and a preparation method thereof. The graphite composite polystyrene material comprises the following raw materials in parts by weight: 80-100 parts of styrene, 5-10 parts of composite graphite, 0.05-0.3 part of an initiator, 3-15 parts of a flame retardant, 3-8 parts of a dispersant and 150-300 parts of water. The composite graphite is prepared from the following raw materials: graphite, nano silicon dioxide and trimethylpropane monoallyl ester; the mass ratio of the graphite to the nano silicon dioxide to the trimethylpropane monoallyl ester is 10: 2: (0.05-0.5). According to the technical scheme, the problem of poor tensile strength of a polystyrene material in related technologies is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a graphite composite polystyrene material and a preparation method thereof. Background Art

[0002] In the field of modern materials science and engineering, the demand for high-performance and multifunctional materials is growing. Polystyrene (PS), as a widely used thermoplastic, has the advantages of light weight, good insulation, and easy processing and molding. It plays an important role in many fields such as packaging, building insulation, and electronic appliances. With the development of modern industry and technology, the performance requirements of polystyrene in many fields are constantly increasing. In automotive interiors, polystyrene is required to have not only good appearance and processing performance, but also sufficient tensile strength to withstand certain external forces to avoid cracking or deformation during use; in the aerospace field, lightweight and high-strength materials are the key to reducing the weight of aircraft and improving flight performance. Although polystyrene is light, its insufficient tensile strength hinders its wider application in this field. Therefore, improving the tensile strength of polystyrene is a problem that needs to be solved at present. Summary of the invention

[0003] The invention provides a graphite composite polystyrene material and a preparation method thereof, which solves the problem of poor tensile strength of the polystyrene material in the related art.

[0004] The technical solution of the present invention is as follows: The present invention provides a graphite composite polystyrene material, comprising the following raw materials in parts by weight: 80-100 parts of styrene, 5-10 parts of composite graphite, 0.05-0.3 parts of initiator, 3-15 parts of flame retardant, 3-8 parts of dispersant, and 150-300 parts of water; The raw materials of the composite graphite include graphite, nano silicon dioxide and trimethylolpropane monoallyl ester; the mass ratio of the graphite, nano silicon dioxide and trimethylolpropane monoallyl ester is 10:2:0.05-0.5.

[0005] As a further technical solution, the mass ratio of the graphite, nano-silicon dioxide and trimethylolpropane monoallyl ester is 10:2:0.1-0.3.

[0006] In the present invention, the mass ratio of graphite, nano-silicon dioxide and trimethylolpropane monoallyl ester is limited to 10:2:0.1-0.3, thereby further improving the tensile strength of the polystyrene material.

[0007] As a further technical solution, the preparation method of the composite graphite comprises the following steps: adding graphite and trimethylolpropane monoallyl ester into a solvent and stirring, drying and then mixing with nano silicon dioxide to obtain the composite graphite.

[0008] As a further technical solution, the solvent is methanol.

[0009] As a further technical solution, the stirring temperature is 30-40° C., and the stirring time is 2-3 h.

[0010] As a further technical solution, the mixing method is mechanical grinding.

[0011] As a further technical solution, the rotation speed of the mechanical grinding is 200 r / min, and the time of the mechanical grinding is 1 hour.

[0012] As a further technical solution, the raw materials of the flame retardant include aluminum hydroxide, dodecyl phosphate, and N2,N2-diallyl melamine.

[0013] In the present invention, the flame retardant composed of aluminum hydroxide, dodecyl phosphate and N2,N2-diallyl melamine improves the flame retardancy of the polystyrene material through the synergistic effect of the three.

[0014] As a further technical solution, the mass ratio of the aluminum hydroxide, dodecyl phosphate and N2,N2-diallyl melamine is 5:1:0.2~0.5.

[0015] In the present invention, the flame retardant properties of the polystyrene material are further improved by limiting the mass ratio of aluminum hydroxide, dodecyl phosphate and N2,N2-diallyl melamine to 5:1:0.2-0.5.

[0016] As a further technical solution, the method for preparing the flame retardant comprises the following steps: adding aluminum hydroxide and dodecyl phosphate to ethanol and mixing, then adding N2,N2-diallyl melamine and stirring, and obtaining the flame retardant after drying.

[0017] As a further technical solution, the mixing temperature is 50° C. and the mixing time is 30 min.

[0018] As a further technical solution, the stirring temperature is 50° C. and the stirring time is 2 h.

[0019] As a further technical solution, the initiator includes one or both of benzoyl peroxide and dicumyl peroxide.

[0020] As a further technical solution, the dispersant includes one or both of polyvinyl alcohol and polyacrylic acid.

[0021] In the present invention, since polyvinyl alcohol or polyacrylic acid has good hydrophilicity and surface activity, adding it to the reaction can form a stable hydration film on the surface of the composite graphite and the flame retardant, prevent agglomeration between particles, and ensure uniform dispersion in the reaction system.

[0022] The present invention also provides a method for preparing a graphite composite polystyrene material, comprising the following steps: S1, mixing water and a dispersant to obtain a mixed solution; S2. Add styrene, composite graphite, initiator and flame retardant into the mixed solution, and obtain graphite composite polystyrene material through suspension polymerization.

[0023] As a further technical solution, the suspension polymerization temperature is 85-95° C., and the suspension polymerization time is 8-9 hours.

[0024] The working principle and beneficial effects of the present invention are: In the present invention, a dispersant is added when preparing a graphite composite polystyrene material, thereby ensuring that styrene, composite graphite, flame retardant and the like can be uniformly dispersed in a system, avoiding agglomeration, and ensuring the uniformity of the material; the addition of the flame retardant improves the flame retardancy of the polystyrene material; composite graphite consisting of graphite, nano-silicon dioxide and trimethylolpropane monoallyl ester is added, and the mass ratio of graphite, nano-silicon dioxide and trimethylolpropane monoallyl ester is limited to 10:2:0.05-0.5, thereby improving the tensile strength of the polystyrene material and solving the problem of poor tensile strength in the prior art. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In the following embodiments and comparative examples: Nano-silicon dioxide, particle size: 50nm; graphite, particle size: 400 mesh; polyvinyl alcohol, model: PVA-205; polyacrylic acid, Mw: 1000.

[0027] Example 1 A method for preparing a graphite composite polystyrene material comprises the following steps: S1, mixing 150 parts of water and 3 parts of polyvinyl alcohol to obtain a mixed solution; S2, adding 80 parts of styrene, 5 parts of composite graphite, 0.05 parts of benzoyl peroxide, and 3 parts of flame retardant to the mixed solution, and performing suspension polymerization at 85° C. for 9 hours to obtain a graphite composite polystyrene material; Preparation method of composite graphite: 20g of graphite and 0.1g of trimethylolpropane monoallyl ester are added to 300mL of methanol, heated to 40°C, mixed and stirred for 2h, dried, and mechanically ground with 4g of nano-silicon dioxide at a speed of 200r / min for 1h to obtain composite graphite; The flame retardant is aluminum hydroxide.

[0028] Example 2 A method for preparing a graphite composite polystyrene material comprises the following steps: S1, mixing 250 parts of water and 5 parts of polyacrylic acid to obtain a mixed solution; S2, adding 90 parts of styrene, 8 parts of composite graphite, 0.15 parts of dicumyl peroxide, and 9 parts of flame retardant to the mixed solution, and performing suspension polymerization at 95° C. for 8 hours to obtain a graphite composite polystyrene material; Preparation method of composite graphite: 20g of graphite and 0.1g of trimethylolpropane monoallyl ester are added to 300mL of methanol, heated to 30°C, mixed and stirred for 3h, dried, and mechanically ground with 4g of nano-silicon dioxide at a speed of 200r / min for 1h to obtain composite graphite; The flame retardant is aluminum hydroxide.

[0029] Example 3 A method for preparing a graphite composite polystyrene material comprises the following steps: S1, mixing 300 parts of water and 8 parts of polyacrylic acid to obtain a mixed solution; S2, adding 100 parts of styrene, 10 parts of composite graphite, 0.3 parts of dicumyl peroxide, and 15 parts of flame retardant to the mixed solution, and performing suspension polymerization at 90° C. for 8 hours to obtain a graphite composite polystyrene material; Preparation method of composite graphite: 20g of graphite and 0.1g of trimethylolpropane monoallyl ester are added to 300mL of methanol, heated to 30°C, mixed and stirred for 3h, dried, and mechanically ground with 4g of nano-silicon dioxide at a speed of 200r / min for 1h to obtain composite graphite; The flame retardant is aluminum hydroxide.

[0030] Example 4 The only difference between this embodiment and embodiment 2 is that the added amount of trimethylolpropane monoallyl ester is 1 g.

[0031] Example 5 The only difference between this embodiment and embodiment 2 is that the added amount of trimethylolpropane monoallyl ester is 0.2 g.

[0032] Example 6 The only difference between this embodiment and embodiment 2 is that the added amount of trimethylolpropane monoallyl ester is 0.6 g.

[0033] Example 7 The difference between this embodiment and embodiment 2 is that the flame retardant is prepared by adding 10 g of aluminum hydroxide and 2 g of dodecyl phosphate into 200 mL of ethanol, heating to 50° C. and mixing for 30 min, and drying to obtain the flame retardant.

[0034] Example 8 The difference between this embodiment and embodiment 2 is that the flame retardant is prepared by adding 10 g of aluminum hydroxide and 2 g of dodecyl phosphate to 200 mL of ethanol, heating to 50° C. and mixing for 30 min, then adding 0.2 g of N2,N2-diallylmelamine and stirring, continuing to mix at 50° C. for 2 h, and drying to obtain a flame retardant.

[0035] Example 9 The only difference between this embodiment and embodiment 8 is that the added amount of N2,N2-diallylmelamine is 1.6 g.

[0036] Example 10 The only difference between this embodiment and embodiment 8 is that the added amount of N2,N2-diallylmelamine is 0.4 g.

[0037] Embodiment 11 The only difference between this embodiment and embodiment 8 is that the added amount of N2,N2-diallylmelamine is 1 g.

[0038] Comparative Example 1 The only difference between this comparative example and Example 1 is that the composite graphite is replaced by an equal amount of graphite.

[0039] Comparative Example 2 The only difference between this comparative example and Example 1 is that the preparation method of the composite graphite is as follows: 20 g of graphite and 4 g of nano-silicon dioxide are mechanically ground at a rotation speed of 200 r / min for 1 h to obtain the composite graphite.

[0040] Comparative Example 3 The only difference between this comparative example and Example 1 is that the preparation method of the composite graphite is as follows: 20 g of graphite and 0.1 g of trimethylolpropane monoallyl ester are added to 300 mL of methanol, heated to 40° C., mixed and stirred for 2 h, and dried to obtain the composite graphite.

[0041] Experimental Example 1 After the graphite composite polystyrene materials obtained in Examples 1 to 6 and Comparative Examples 1 to 3 were extruded into sheets, the tensile strength was tested according to the method in GB / T1040.1-2018 "Determination of Tensile Properties of Plastics Part 1: General Principles", with a tensile rate of 5 mm / min. The test results are shown in Table 1.

[0042] Table 1 Tensile strength test results of graphite composite polystyrene materials

[0043] It can be seen from Table 1 that, compared with Comparative Examples 1 to 3, the tensile strength of the graphite composite polystyrene material prepared in Examples 1 to 6 is higher than that of Comparative Examples 1 to 3, indicating that when a composite graphite composed of graphite, nano-silica and trimethylolpropane monoallyl ester is added during the preparation process and the mass ratio of graphite, nano-silica and trimethylolpropane monoallyl ester is limited to 10:2:0.1 to 0.3, the tensile strength of the graphite composite polystyrene material can be further improved.

[0044] Experimental Example 2 After the graphite composite polystyrene material base prepared in Example 2 and Examples 7 to 11 was formed into sheets, the oxygen index was measured according to the method in GB / T2406.2-2009 "Oxygen Index Method for Determination of Combustion Behavior of Plastics Part 2: Room Temperature Test", and the test results are shown in Table 2.

[0045] Table 2 Test results of flame retardant properties of graphite composite polystyrene materials

[0046] It can be seen from Table 2 that the oxygen index of the graphite composite polystyrene material prepared in Examples 8 to 11 is higher than that in Example 2 and Example 7, indicating that when the flame retardant is composed of aluminum hydroxide, dodecyl phosphate and N2, N2-diallyl melamine, and the mass ratio of aluminum hydroxide, dodecyl phosphate and N2, N2-diallyl melamine is 5:1:0.2 to 0.5, the flame retardancy of the graphite composite polystyrene material can be further improved.

[0047] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A graphite composite polystyrene material, characterized in that: The raw materials include the following components in parts by weight: 80-100 parts of styrene, 5-10 parts of composite graphite, 0.05-0.3 parts of initiator, 3-15 parts of flame retardant, 3-8 parts of dispersant, and 150-300 parts of water; The raw materials of the composite graphite include graphite, nano silicon dioxide and trimethylolpropane monoallyl ester; the mass ratio of the graphite, nano silicon dioxide and trimethylolpropane monoallyl ester is 10:2:0.05-0.

5.

2. A graphite composite polystyrene material according to claim 1, characterized in that: The mass ratio of the graphite, nano-silicon dioxide and trimethylolpropane monoallyl ester is 10:2:0.1-0.

3.

3. The graphite composite polystyrene material according to claim 1, characterized in that: The preparation method of the composite graphite comprises the following steps: adding graphite and trimethylolpropane monoallyl ester into a solvent and stirring, drying and then mixing with nano silicon dioxide to obtain the composite graphite.

4. A graphite composite polystyrene material according to claim 3, characterized in that: The stirring temperature is 30-40° C., and the stirring time is 2-3 h.

5. The graphite composite polystyrene material according to claim 3, characterized in that: The solvent is methanol.

6. The graphite composite polystyrene material according to claim 1, characterized in that: The raw materials of the flame retardant include aluminum hydroxide, dodecyl phosphate and N2,N2-diallyl melamine.

7. The graphite composite polystyrene material according to claim 6, characterized in that: The mass ratio of the aluminum hydroxide, dodecyl phosphate and N2,N2-diallyl melamine is 5:1:0.2-0.

5.

8. The graphite composite polystyrene material according to claim 1, characterized in that: The initiator includes one or both of benzoyl peroxide and dicumyl peroxide.

9. The graphite composite polystyrene material according to claim 1, characterized in that: The dispersant includes one or both of polyvinyl alcohol and polyacrylic acid.

10. The method for preparing a graphite composite polystyrene material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, mixing water and a dispersant to obtain a mixed solution; S2. Add styrene, composite graphite, initiator and flame retardant into the mixed solution, and obtain graphite composite polystyrene material through suspension polymerization.

Citation Information

Patent Citations

  • Golf balls including crosslinked thermoplastic polyurethane

    CN102311636A

  • Preparation method of morphology-controllable transparent monodisperse nano-zirconia liquid phase dispersion

    CN110577241A

  • Halogen-free flame retardant namely expandable polystyrene particle and preparation method thereof

    CN110804203A

  • Graphite composite polystyrene particle and preparation method thereof

    CN116574341A

  • Flame retardant for TPU charging pile and preparation method thereof

    CN118852732A